Rodents as Sentinels for the Prevalence of Tick-Borne Encephalitis Virus - Achazi, K.; Ruzek, D.; Donoso-Mantke, O.; Schlegel, Matthias; Sheikh Ali, Hanan; Wenk, M.; Schmidt-Chanasit, J.; Ohlmeyer, L.; Ruhe, F.; Vor, T.; Kiffner, C.; Kallies, R.; et al. (Vector-Borne and Zoonotic Diseases, 2011)
Introduction: Tick-borne encephalitis virus (TBEV) causes one of the most important flavivirus infections of the central nervous system, affecting humans in Europe and Asia. It is mainly transmitted by the bite of an infected tick and circulates among them and their vertebrate hosts. Until now, TBE risk analysis in Germany has been based on the incidence of human cases. Because of an increasing vaccination rate, this approach might be misleading, especially in regions of low virus circulation. Method: To test the suitability of rodents as a surrogate marker for virus spread, laboratory-bred Microtus arvalis voles were experimentally infected with TBEV and analyzed over a period of 100 days by real-time (RT)-quantitative polymerase chain reaction. Further, the prevalence of TBEV in rodents trapped in Brandenburg, a rural federal state in northeastern Germany with autochthonous TBE cases, was determined and compared with that in rodents from German TBE risk areas as well as TBE nonrisk areas. Results: In experimentally infected M. arvalis voles, TBEV was detectable in different organs for at least 3 months and in blood for 1 month. Ten percent of all rodents investigated were positive for TBEV. However, in TBE risk areas, the infection rate was higher compared with that of areas with only single human cases or of nonrisk areas. TBEV was detected in six rodent species: Apodemus agrarius, Apodemus flavicollis, Apodemus sylvaticus, Microtus agrestis, Microtus arvalis, and Myodes glareolus. M. glareolus showed a high infection rate in all areas investigated. Discussion and Conclusion: The infection experiments proved that TBEV can be reliably detected in infected M. arvalis voles. These voles developed a persistent TBE infection without clinical symptoms. Further, the study showed that rodents, especially M. glareolus, are promising sentinels particularly in areas of low TBEV circulation